Bilateral aplastic testes in adult buffalo bull (Bubalus bubalis) - ARANGASAMY, A; SINGH, R; SINGH, L P (The Indian Journal of Animal Reproduction, 2023)
Out of seventy male genetalia, obtained from local abattoir, one case of bilateral testicular aplasia was observed. Both the testes were absenL Though the epididymis and vas difference were intact, the former was hypertrophied as compared to control. The epididymal fluid did not show any spermatozoa on microscopical examination. On histological examination. the hypertrophied epididymia in the present case was observed due to thickened smooth muscle layers and connective tissues around the ill developed mucosa which might be due to absence of steroidal hormones.